2012
DOI: 10.1021/am300149u
|View full text |Cite
|
Sign up to set email alerts
|

Electrorheology of Polystyrene Filler/Polyhedral Silsesquioxane Suspensions

Abstract: An important challenge in the field of electrorheology is identifying low-viscosity fluids that would exhibit significant changes in viscosity, or a yield stress, upon the application of an external electric field. Our recent research showed that optimal compositions of mixtures, 10 wt % sulfonated polyhedral oligomeric silsesquioxanes (s-POSS) mixed with polydimethyl siloxane (PDMS), exhibited significant electrorheological activity. Here we show that s-POSS/PDMS mixtures containing polystyrene (PS) fillers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 26 publications
0
29
1
Order By: Relevance
“…Under an applied electric field, the particles are polarized due to dielectric constant mismatch between the particles and medium. 19,20 The ER performance is known to be related to the particle shape, size and dielectric properties. [8][9][10][11] Many conducting polymers, such as polyaniline (PANI) and polypyrrole (PPy), exhibit ER behaviours when they are dedoped in a semi-conducting regime from 10 À5 S cm À1 to 10 À9 S cm À1 .…”
Section: Introductionmentioning
confidence: 99%
“…Under an applied electric field, the particles are polarized due to dielectric constant mismatch between the particles and medium. 19,20 The ER performance is known to be related to the particle shape, size and dielectric properties. [8][9][10][11] Many conducting polymers, such as polyaniline (PANI) and polypyrrole (PPy), exhibit ER behaviours when they are dedoped in a semi-conducting regime from 10 À5 S cm À1 to 10 À9 S cm À1 .…”
Section: Introductionmentioning
confidence: 99%
“…The interfacial adsorption of a layer of dipolar molecules onto the surface of PS particles in a PDMS medium changed a previously ER inert suspension (PS/PDMS) to a viable ER fluid: s-POSS/PS/PDMS. In the subsequent study, they showed that by adding small concentrations (less than 2 wt%) of s-POSS to the ER fluid, sulfonated-PS (s-PS)/PDMS, resulted in the formation of a superior ER suspension, s-POSS/s-PS/PDMS, exhibiting a significant improvement in ER activity of over 200% at moderate fields [41]. This behavior was not readily rationalized in terms of current ER theories, which suggests that the properties of the shell, dielectric and conductive, largely determine the yield stress of the system.…”
Section: Fabrication and Field Responsementioning
confidence: 99%
“…Electrorheological (ER) fluids are suspensions of polarizable particles dispersed in insulating medium oils. Under the applied electric fields, the colloidal particles instantly attract one another to form solidlike networks along the direction of an applied electric fields . When the electric field is off, the aggregates are reversibly dispersed.…”
Section: Introductionmentioning
confidence: 99%
“…To be electrorheologically active, the suspended particle should be polarized under the electric field. For non‐polarizable or weakly polarizable particles such as polymer particles or silica microspheres, coating on the surfaces of the particles with a more polarizable or conducting materials can be a useful strategy . The core–shell type particles can get higher permittivity component compared to the insulating medium.…”
Section: Introductionmentioning
confidence: 99%